Baseball Great - Green, Tim 1963- (New York : HarperCollinsPublishers, 2009)
All twelve-year-old Josh wants to do is play baseball, but when his father, a minor league pitcher, signs him up for a youth championship team, Josh finds himself embroiled in a situation with potentially illegal consequences.
Keywords: Baseball -- Fiction; Father-son relationship -- Fiction; Middle schools -- Fiction; Drug traffic -- Fiction; School stories